Blood pact - Hagberg, David (New York : Forge, 2015)
A large amount of the treasure stolen by conquistadors of the eighteenth century was buried in southern New Mexico, and Jacob Ambli, a Catholic priest, was sent on a Spanish mission to find seven caches left for the Church. He kept a diary of the locations, but was murdered and the journal was lost. Now, years later, the diary has come to light.
Keywords: Thieves -- Fiction; Suspense fiction